2007
DOI: 10.1007/s00709-007-0271-x
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of programmed cell death during early senescence of barley leaves: possible role of nitric oxide

Abstract: Leaf senescence is a highly coordinated process which involves programmed cell death (PCD). Early stages of leaf senescence occurring during normal leaf ontogenesis, but not triggered by stress factors, are less well known. In this study, we correlated condensation of chromatin and nuclear DNA (nDNA) fragmentation, two main features of PCD during early senescence in barley leaves, with the appearance of nitric oxide (NO) within leaf tissue. With the help of the alkaline version of the comet assay, together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…5) suggesting a cytotoxic effect of SNP. Cytotoxicity and cell death are known actions of NO, especially when it is present in high concentrations (Delledonne et al 1998;Clarke et al 2000;Zottini et al 2002;Víteček et al 2007;Kolodziejek et al 2007). Our findings suggest that a concentration of 1,000 lM of SNP induced soybean root cell death, reducing its growth and lignification.…”
Section: Discussionmentioning
confidence: 99%
“…5) suggesting a cytotoxic effect of SNP. Cytotoxicity and cell death are known actions of NO, especially when it is present in high concentrations (Delledonne et al 1998;Clarke et al 2000;Zottini et al 2002;Víteček et al 2007;Kolodziejek et al 2007). Our findings suggest that a concentration of 1,000 lM of SNP induced soybean root cell death, reducing its growth and lignification.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have described the mechanism of PCD during plant leaf senescence, and have mainly focused on biotic and abiotic stress (Lee and Chen 2002;Buchanan-Wollaston et al 2003;Penfold and Buchanan-Wollaston 2014;Potschin et al 2014;Sakamoto and Takami 2014). These stresses are often inextricably linked with reactive oxygen species (ROS), such as dark (Pastori and Delrio 1994a, b;Jimenez et al 1997;del Rio et al 2003), Drought (Hameed et al 2013;Ye et al 2013), heat (Fan and Xing 2004), NO (Kolodziejek et al 2007;Guo et al 2013), O 3 (Pell et al 1999), paraquat and H 2 O 2 (Pastori and Trippi 1993), salt stress (Deng et al 2014), and UV-C irradiation (Danon and Gallois 1998). Increasing evidence has revealed that ROS can also act as a signal molecule or take part in PCD, resulting in delayed growth (Lamb and Dixon 1997;Bowler and Fluhr 2000;Bethke and Jones 2001;Noreen and Ashraf Advanced Online Publication 2015Doi:10.101660977-1 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The type of DNA fragmentation can be also distinguished in comet assay [ 28 , 39 ]. Regardless of the method (alkaline or neutral variant), intact DNA remains in the head of the comet and DNA from regions with strand breaks appears in the tail.…”
Section: Resultsmentioning
confidence: 99%
“…amount of DNA in the comet tail) times tail length (i.e. length of the comet tail measured from right border of head area to end of tail, according to the method described by Olive et al [ 27 ] and Kołodziejek et al [ 28 ]). We analyzed 30 images of nuclei from each experimental series.…”
Section: Methodsmentioning
confidence: 99%